Do they understand? : English trials heard by chinese jurors in the Hong Kong Courtroom - Ng, Eva (Language and Law / Linguagem e Direito, 2017)
Trial by jury is a key institution in the common law system. The introduction of lay persons into the judicial process, however, gives cause for concern about jurors’ comprehension of legal language. Studies conducted in America reveal that many jurors are unable to fully understand pattern jury instructions due to the linguistic features typical of legalese, which to some sounds like a foreign language. Now, what if these instructions and legal speeches are uttered in a language that is non-native to the jurors? This is common scenario in the Hong Kong courtroom, where trials conducted in English are typically heard by Chinese jurors. Until now, only one survey conducted in the early 1990s has shed light on this issue. Drawing on the recordings of two jury trials from the High Court, and one Appellate Court judgment quashing a jury verdict, the present study provides further empirical evidence supporting claims about jurors’ comprehension problem. Failure to address this problem jeopardises not just the administration of justice, but the very survival of the jury system in Hong Kong. This paper proposes ways to improve jurors’ access to legal speeches in particular and the entire trial in general in order to help them return a more soundly based verdict